Analisis Hubungan Nilai SPAD Dengan Nilai Indeks Vegetasi pada Tanaman Padi yang Terserang Penyakit BlasMenggunakan Citra Multispektral - Gede Suyoga Arista Putra; I Made Anom Sutrisna Wijaya; Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Blast disease is a disease that attacks the leaves of rice plants. Blast disease attacks can affect chlorophyll and the health of rice plants. Leaf chlorophyll can be estimated using a SPAD chlorophyll meter to obtain the SPAD value. The vegetation index v alue has a strong relationship with chlorophyll. This study aims to obtain the relationship between SPAD value and Vegetation Index value in rice plants affected by blast disease using multispectral imagery and determine the level of correlation between SP AD value and Vegetation Index value in rice plants affected by blast disease using multispectral imagery. SPAD value sampling was carried out on 3 rice field plots, each plot was taken 5 points diagonally, and each point was taken 9 rice paddy clumps. Next , multispectral image acquisition using the DJI Phantom 4 Drone with multispectral cameras at altitudes of 15 m, 30 m, and 45 m. The image is then mosaiced using Agisoft Metashape, then normalized with Photoshop. Next, the vegetation index analysis of NDVI , CI G , and SAVI using QGIS 3.16, followed by regression analysis between the SPAD value and the vegetation index value. The results of the analysis showed that the three vegetation indices at various altitudes produced a linear relationship and the degree of correlation ranged from strong to very strong. Strong correlation rate on NDVI 45 m (65.4%), SAVI 45 m (63.1%), and very strong correlation on NDVI index 15 m (94.2%), 30 m (79.5%), CI G 15 m (80.5%), 30 m (84.8%), 45 m (82.5%), and SAVI 15 m (80.5%), 30 m (78%). It can be concluded that the NDVI vegetation index with a height of 15 m provides the strongest correlation value